Nature's Wild : Love, Sex, and Law in the Caribbean - Gosine, Andil, 1973- (Book collections on Project MUSE., 2021)
"Andil Gosine revises understandings of queer desire in the Caribbean, showing how the very concept of homosexuality in the Caribbean (and in the Americas more broadly) has been overdetermined by a colonially-influenced human/animal divide."--